Time to Antiarrhythmic and Association with Return of Spontaneous Circulation in the United States. (17th February 2023) - Huebinger, Ryan; Chan, Hei Kit; Bobrow, Bentley; Chavez, Summer; Schulz, Kevin; Gordon, Richard; Jarvis, Jeffrey
Abstract: Introduction: Recent clinical trials have failed to identify a benefit of antiarrhythmic administration during cardiac arrest. However, little is known regarding the time to administration of antiarrhythmic drugs in clinical practice or its impact on return of spontaneous circulation (ROSC). We utilized a national EMS registry to evaluate the time of drug administration and association with ROSC. Methods: We utilized the 2018 and 2019 NEMSIS datasets, including all non-traumatic, adult 9-1-1 EMS activations for cardiac arrests with initial shockable rhythm and that received an antiarrhythmic. We calculated the time from 9-1-1 call to administration of antiarrhythmic. We excluded cases with erroneous time stamps. Stratified by initial antiarrhythmic (amiodarone and lidocaine), we created a mixed-effect logistic regression model evaluating the association between every 5-minute increase in time to antiarrhythmic and ROSC. We modeled EMS agency as a random intercept and adjusted for confounders. Results: There were 449, 630 adults, non-traumatic cardiac arrests identified with 11, 939 meeting inclusion criteria. 9, 236 received amiodarone and 1, 327 received lidocaine initially. The median time in minutes to initial dose for amiodarone was 19.9 minutes (IQR 15.8–25.6) and for lidocaine was 19.5 minutes (IQR 15.2–25.4). Increasing time to initial antiarrhythmic was associated with decreased odds of ROSC for both amiodarone (aOR 0.9; 95% CI 0.9–0.94) and lidocaine (aOR 0.9; 95% CI 0.8–0.97). Conclusion: Time to administration of anti-arrhythmic medication varied, but most patients received the first dose of anti-arrhythmic drug more than 19 minutes after the initial 9-1-1 call. Longer time to administration of an antiarrhythmic in patients with an initial shockable rhythm was associated with decreased ROSC rates.